Students' Perceptions toward Utilizing Technology to Help Reading Skills: A Case Study of IFL Students in One Public University in Battambang - Soeurn Chenda; Ly Sovannarath; Vann Rachel (UNIB Press, 2024)
Technology is essential in both today's society and the education system. Learners can use technology to investigate further resources to build up their English language skills, especially reading skills. Reading skills make our minds learn how to analyze the information in the text. This study aims to: 1) explore students’ perceptions toward utilizing technology to improve their reading skills; 2) study factors that encourage students to use technology to improve their reading skills; and 3) explore students’ suggestions to use technology to improve their reading skills. Mixed-methods research was used in this study to collect data. 128 participants were randomly selected to participate, and 6 of the 128 students were randomly chosen to seek deeper information in the interview with qualitative data. Statistical analysis was used in Excel to analyze the quantitative data, while thematic analysis was used to analyze the qualitative data. This study showed that participants had positive opinions toward utilizing technology to improve their reading skills. Moreover, technology helps them a lot, especially with their reading skills, where they can practice their pronunciation, read online, learn new vocabulary, etc. However, they faced some problems, including financial problems while using the technology, connection problems, a lack of technology information, and technical problems. But there were some good suggestions, such as the right way to use technology and how technology is important to our society. To conclude, technology can help students strengthen their reading skills.